מה זה -2 G (g ^ 3h ^ 5)?

מה זה -2 G (g ^ 3h ^ 5)?
Anonim

תשובה:

ראה תהליך פתרון בהמשך:

הסבר:

ראשית, לשכתב את הביטוי כמו:

# -2 (g * g ^ 3) (h * h ^ 5) #

לאחר מכן השתמש בכללים אלה עבור מעריכים כדי לפשט את הביטוי:

#a = a ^ color (אדום) (1) # ו # x ^ צבע (אדום) (א) xx x ^ צבע (כחול) (b) = x ^ (צבע (אדום) (א) + צבע (כחול) (b)) #

מס '2 - (g ^ צבע (אדום) (1) * g ^ צבע (כחול) (3)) (h צבע (אדום) (1) * h צבע (כחול) (5)) => #

# (2) צבע (אדום) (1) + צבע (כחול) (3)) h (צבע) (אדום) (1) + צבע (כחול) (5)) => #

# -2g ^ 4h ^ 6 #